Applied Statistics Module Version 3 - Siti Zanariah, Satari; Noryanti, Muhammad; Siti Roslindar, Yaziz; Nor Hafizah, Moslim; Roslinazairimah, Zakaria; Farahanim, Misni (Penerbit Universiti Malaysia Pahang, 2018)
This module is intended to facilitate teaching and learning of Statistics courses in colleges and universities at degree level. It is specially tailored for students of science, engineering and technology. This book provides examples and exercises that present important ideas of statistics in a realistic setting to show connections between theory and application in industry and scientific research. The materials in this module also integrate well with statistical software packages especially in the topics on descriptive statistics, graphical summary, hypothesis testing, analysis of variance and regression models. The use of Microsoft Excel is emphasised in this module.